Indonesian Coast Guard Personnel Contemporary Strategy through Coast Guard Basic Training and Officer Formation in Realizing Digital Leadership Era 5.0 - Aliyah, Yurizki; Susmoro, Harjo; Alam, Tasdik Mustika; Patmi, Sri; Prakoso, Lukman Yudho (Formosa Journal of Applied Sciences, 2024)
This study analyzes the Contemporary Strategy of Bakamla Personnel through Coast Guard Basic Training and Officer Formation in Realizing Digital Leadership Era 5.0. In this study, the author analyzes various contributing factors and challenges to Coast Guard Basic Training and Officer Formation in Realizing Digital Leadership Era 5.0. This research is descriptive with a qualitative approach, where initially the author explained about Digital Leadership Era 5.0. After that, the author discussed Coast Guard Basic Training and Officer Formation in Realizing Digital Leadership Era 5.0.  Next, the author describes the steps that Bakamla can take. In an effort to realize the Digital leadership generation in the 5.0 era, it is important to improve the training and education of Bakamla personnel through Coast Guard Basic Training.